The ideology of semiosis in Romanian prose under communism - Goldiş, Alex (Primerjalna književnost, 2016)
The article discusses the confrontation of the poetics of mimesis, directed towards nonlinguistic events, with that of semiosis, concerned with the production of signs, in literature under censorship. The case of Romanian fiction in the 1980s is representative of the "textual resistance" specific to East European Postmodernism.
Keywords: ideologija; romunska književnost; communism; komunizem; cenzura; metafikcija; postmodernizem; ezopski jezik; semioza; subverzivnost